Transcriptome and Metabolome Jointly Revealed the Regulation and Pathway of Flower and Pod Abscission Caused by Shading in Soybean (Glycine max L.) - Hexiang Sun; Dexin He; Nan Wang; Xingdong Yao; Futi Xie (Agronomy, 2023)
Flowers and pod abscission significantly reduces soybean yield. This study aims to identify the main signaling pathways and key candidate genes in soybean leaves that affect flower and pod abscission under shade conditions. This information will be useful for the localization and cloning of genes related to abscission. Two soybean cultivars with different abscission rates (Liaodou 32 and Shennongdou 28) were used in this experiment. The soybean leaves were subjected to 50% shading treatment and the transcriptome and metabolome was sequenced during the light-sensitive period. The effects of weak light at different growth stages on the metabolic pathways of soybean leaves and organ abscission were investigated by analyzing plant phenotype and physiological changes. The results showed that both two cultivars triggered the same molecular mechanism and similar metabolite accumulation mode by shading, but the regulations of the two cultivars were different. The key candidate genes identified for soybean flower and pod abscission caused by shading were DIV, MYB06, MYB44, MY1R1, MYBS3, WRKY6, WRK53, WRK70, WRK40, DOF14, CDF3, CDF2, GATA5, DREB3 and ERF3; the differentially expressed genes that caused the variation between the cultivars were SRM1, MYB16, WRK24, COL16, MYB61 and TRB1. The main metabolic pathways involved in soybean flower and pod abscission caused by shading were secondary metabolite biosynthesis pathway, metabolic pathway, cofactor biosynthesis pathway, phenylpropanoid biosynthesis pathway, flavonoid biosynthesis pathway, fatty acid biosynthesis pathway and amino acid biosynthesis pathway; the DEMs that caused the differences among the cultivars were carbon metabolism, glutathione metabolism, biotin metabolism, nucleotide metabolism, purine metabolism, plant hormone signaling, flavone and flavonol biosynthesis, lysine degradation, arginine and proline metabolism, amino sugars and nucleotide sugars metabolism, etc. In conclusion, shading treatment in the light-sensitive period of soybean changed the physiological response and gene expression level of leaves, inhibited carbohydrate metabolism and transport and biosynthesis of secondary metabolites, and thereby leading to increased competition and hormonal disruption, which promoted the abscission of soybean flowers/pods and reduced grain yield.